2009
DOI: 10.1080/15532730902799938
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Considerations for the World Professional Association for Transgender Health'sStandards of Care: The Asian Perspective

Sam Winter

Abstract: This article begins by portraying the nature of the Asian transgender experience, paying particular attention to transprejudice as a health issue, and the possible role of pathologization of gender variance in prompting and supporting transprejudice. It then outlines the range of transgender health care provision available in Asia. The article ends with seven recommendations for the seventh revision to the World Professional Association for Transgender Health's (WPATH) Standards of Care (SOC-7). The first four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 23 publications
0
32
0
3
Order By: Relevance
“…First, the prevalence of gender dysphoria and gender change among DSD individuals is considerably higher than that of GID in the general population, although there are considerable differences between syndromes (see below). This conclusion is largely based on data from estimates of GID in Western societies but would remain even if based on the apparently higher prevalence figures of Asian societies as reported by Winter (2009). Secondly, though the DSM as developed in Western cultures distinguishes two different categories of GID in terms of age of onset, one characterized by early childhood onset, the other by onset in adulthood (frequently with antecedent fetishistic cross-dressing without GID during adolescence), gender dysphoria and gender change in DSD individuals can gradually emerge at any age, although the likelihood of gender change appears to be lower after puberty (de Vries & Cohen-Kettenis, 2009).…”
Section: Differences In Epidemiologymentioning
confidence: 79%
“…First, the prevalence of gender dysphoria and gender change among DSD individuals is considerably higher than that of GID in the general population, although there are considerable differences between syndromes (see below). This conclusion is largely based on data from estimates of GID in Western societies but would remain even if based on the apparently higher prevalence figures of Asian societies as reported by Winter (2009). Secondly, though the DSM as developed in Western cultures distinguishes two different categories of GID in terms of age of onset, one characterized by early childhood onset, the other by onset in adulthood (frequently with antecedent fetishistic cross-dressing without GID during adolescence), gender dysphoria and gender change in DSD individuals can gradually emerge at any age, although the likelihood of gender change appears to be lower after puberty (de Vries & Cohen-Kettenis, 2009).…”
Section: Differences In Epidemiologymentioning
confidence: 79%
“…Persons with varying degrees of gender-atypical development have been described for many and diverse cultures (e.g., Herdt, 1996; Whitam, 1997; Winter, 2009; for Brazil: Cardoso, 2005; Inciardi et al, 1999; Kulick, 1998; for India: Bradford, 1983; Nanda, 1999; for India and Sri Lanka: Stevenson, 1974; for Mexico: Stephen, 2002; for Myanmar: Coleman et al, 1992; for Oman: Wikan, 1977; for Samoa: Bartlett & Vasey, 2006; Vasey & Bartlett, 2007; for Thailand: Costa and Matzner, 2007; Jackson, 1997; for the native Zuni culture in the U.S.: Roscoe, 1990) and throughout recorded history (Bullough & Bullough, 1993; Feinberg, 1996; Perry, 1987; Rowsen, 1991; Wiesner-Hanks, 2001). In American society, the extreme variant involving gender reassignment, cross-gender hormone treatment, and genital surgery became a salient issue with George/Christine Jorgensen in 1952 (Docter, 2007; Hamburger, Stürup, & Dahl-Iversen, 1953), which was soon followed by clinical benchmark papers and books on the subject: Benjamin (1954); Green & Money (1960); Stoller (1964); Pauly (1965); Benjamin (1966); Green & Money (1969).…”
Section: History Of Gender Variants In the Dsmmentioning
confidence: 99%
“…In fact, GID of childhood is a stronger predictor of the development of homosexuality than of GID in adolescence or adulthood (Bailey & Zucker; 1995; Mathy & Drescher, 2008), which, however, does not justify to conceptually equate GID and homosexuality, given their different developmental courses and frequent non-congruence. Finally, both homosexuals and people with GIVs suffer extensive societal stigma and, probably in part as a consequence, increased psychiatric problems (Alanko et al, 2009; Lombardi, Wilchins, Priesing, & Malouf, 2001; Meyer & Northridge, 2007; Nuttbrock et al, 2009; Plöderl & Fartacek, 2009; Ryan, Huebner, Diaz, & Sanchez, 2009; Winter, 2009), although bidirectional causation cannot be ruled out. On the other hand, there is a subgroup of persons with early-childhood GIV who settle into their assigned gender during later childhood and, relative to their natal gender, develop heterosexuality.…”
Section: History Of Gender Variants In the Dsmmentioning
confidence: 99%
“…Research suggests the transitions in self and identity for transgender people occur earlier in life in Asia compared to North America and Europe (Winter, 2009). Studies have shown transgender youth experience substantial victimization (Garofalo, R., Deleon, J., Osmer, E., Doll, M., & Harper, G. W., 2006;Stieglitz, 2010).…”
Section: Vietnammentioning
confidence: 99%